Pengembangan Lembar Kerja Siswa Berbasis Pendekatan Kontekstual pada Materi Lingkaran Untuk Siswa SMP - Gitriani, Reva; Aisah, Siti; Hendriana, Heris; Herdiman, Indri (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2018)
This research aims to develop learning tools of mathematics junior high school with a contextual approach as a tool for learning mathematics. The subjects are 34 students in the eighth grade of junior high school. The research method used is development research by referring to ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The instruments are validation sheets of student worksheet, questionnaires, and test results. Results of this research are: (1) the validation result of student worksheet is in very good category; (2) the result of a questionnaire of student response is in very good category; and (3) the result of the students learning test is in a good category. So that, student worksheet is feasible from the aspect of validity, practicality, and effectiveness.